THE GAME OF BEAUTY AND SENSITIVITY IN SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2012)
In this article we explore the School physical education developed by physical education teachers in perspective of development of children's sensitivity. This is a reflection that is based on the thematic, bodiness, playfulness and of the game, which is evidenced from a specialization course in physical education for children. Thus, we note the following considerations: there is a need of the redemption of sensitivity and developing playfulness as a movement to be sought and an invitation to teachers of physical education for a trip to the seas of knowledge emanating from the body and need to be further explored in the various archipelagos of the senses, feelings, emotions that are expressed in under construction; Have an understanding of playful as a human dimension that is inherent in every human being; The development of reflective practice enables sensitivity and should be worked through games, jokes, gymnastics, dance and sports; A physical education for the development of sensitivity requires sensitive teachers therefore requires more attention by the institutions-forming physical education teachers.